Model Pengembangan Kompetensi Guru Madrasah Aliyah - Abdul Madjid (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2014)
This research seeks to: describe teacher competence and proposes a hypothetic model for teacher competence development in Madrasah Aliyah of Yogyakarta. This article uses Research Development (R D) method to design techer competence development model, and data collection is based on questionaries, interview and Focus Group Discussion (FGD). Some aspects of teacher competence measured in this research include: paedagogical competence, personal competence, professional competence, and social competence. The result shows that some aspects of the teacher competences in the Madrasah that are still need to be improved are as follow: 1) Paedagogical competence. The Madrasah teachers in Yogyakarta are still need to improve their capacity in facilitating students’ ability in actualizing and expressing their their potential and capacity; 2) Personal competence. The teachers needs to improve and develop their self-government and self-descipline in a professional way; 3) Professional competence. The teachers need to develop their aptitude and professionalism sustainably in order to conduct a reflective action and be able to use iformation technology during the course of teaching-learning process; 4) Social competence. The teachers need increase their skill in communicating with their collagues and among the academic communities. Ketwords: Teacher competence, the madrasah, education, teaching-learning development.